Manufactures Building with the Formal Gardens in the foreground, Alaska Yukon Pacific Exposition, Seattle, June 1909. - Nowell, Frank H., 1864-1950 (1909)
Ph Coll 727.462 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number